(3GdahGFO aj GNJUGQ GdebGUOs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Gddg CQSd GdQSd hCfRd GdcJH dEbGeI eUGdM GdOfjG hGdBNQI s
(3BNQgG (B:s
(3bHd ehJg HdMXI cef CbGeG Ydi GdcaQ jhekG Ch TgQ Ch eGjI YGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGRgQ (B(944) s
Keywords: (3CUhd Gdabgs